Comparing heart rate variability biofeedback and simple paced breathing to inform the design of guided breathing technologies - Tabor, Aaron; Bateman, Scott; Scheme, Erik J.; schraefel, m.c. (Frontiers in Computer Science, 2022)
A goal of inbodied interaction is to explore how tools can be designed to provide external interactions that support our internal processes. One process that often suffers from our external interactions with modern computing technology is our breathing. Because of the ergonomics and low-grade-but-frequent stress associated with computer work, many people adopt a short, shallow breathing pattern that is known to have a negative effect on other parts of our physiology. Breathing guides are tools that help people match their breathing patterns to an external (most often visual) cue to practice healthy breathing exercises. However, there are two leading protocols for how breathing cues are offered by breathing guides used in non-clinical settings: simple paced breathing (SPB) and Heart Rate Variability Biofeedback (HRV-b). Although these protocols have separately been demonstrated to be effective, they differ substantially in their complexity and design. Paced breathing is a simpler protocol where a user is asked to match their breathing pattern with a cue paced at a predetermined rate and is simple enough to be completed as a secondary task during other activities. HRV-b, on the other hand, provides adaptive, real-time guidance derived from heart rate variability, a physiological signal that can be sensed through a wearable device. While the benefits of these two protocols have been well established in clinical contexts, designers of guided breathing technology have little information about whether one is better than the other for non-clinical use. To address this important gap in knowledge, we conducted the first comparative study of these two leading protocols in the context of end-user applications. Our findings indicate that the exercises did not significantly differ in their immediate outcomes – both provided similar acute positive physiological effects. Our paper contributes new findings suggesting that paced breathing – a straightforward, intuitive, and easy-to-design breathing exercise – provides the same immediate benefits as HRV-b, but without its added design complexities.